Evaluation of the effectiveness of abate™ used for the treatment of community drinking ponds in the Nigeria guineaworm eradication program (2005)
A study was carried out to ascertain the effectiveness of the Abate™ (0-0-0(1)-0(1)-tetramethyl - 0-0(1)-thiodi-P-phenylene phosphorothiote) an organophosphorous compound used for the treatment of community drinking ponds in the Nigeria Guinea Worm Eradication Programme in South-West Zone of Nigeria. The Abate™ was used in treating 3 large rectangular concrete tanks lined with pond mud, and filled with pond water harbouring cyclops, the crustacean vector of guinea worm disease. A fourth tank containing untreated water served as control. The initial and final cyclops populations of each tank was determined daily for seven days and then weekly up to the 28th day after Abate™ treatment. The standard concentration used in guinea worm eradication program (0.1ml of Abate™ to 50 litres of water) was added. At this concentration, cyclops is known to become paralysed within 72 hours. It was deduced that the population of cyclops, Thermocydops decipiens, was not effectively controlled since it took more than 5, 6 and 14 days to eliminate them from tanks A, B and C respectively. The population of cyclops however, increased in the control tank over the study period. In the control of guinea worm disease vectors, it is necessary to take into cognisance the potency of the chemical used in order to achieve the desired result.